2022
DOI: 10.1523/jneurosci.1622-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Causal Evidence for the Multiple Demand Network in Change Detection: Auditory Mismatch Magnetoencephalography across Focal Neurodegenerative Diseases

Abstract: Title: Causal evidence for the multiple demand network in change detection: auditory mismatch magnetoencephalography across focal neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 105 publications
(168 reference statements)
0
9
0
Order By: Relevance
“…We chose to use a reflexive, pre-attentive measure of gap detection: gap-PPI of the acoustic startle response. PPI, a measure of detection rather than perception, is not influenced by attentional factors provided the interval between stimulus and startle is ≤ 60 ms (Li et al, 2009), but see (Cope et al, 2022). This allows measurement of auditory processing without the potentially confounding contribution of cognition or attention, both of which can be affected by stress.…”
Section: Resultsmentioning
confidence: 99%
“…We chose to use a reflexive, pre-attentive measure of gap detection: gap-PPI of the acoustic startle response. PPI, a measure of detection rather than perception, is not influenced by attentional factors provided the interval between stimulus and startle is ≤ 60 ms (Li et al, 2009), but see (Cope et al, 2022). This allows measurement of auditory processing without the potentially confounding contribution of cognition or attention, both of which can be affected by stress.…”
Section: Resultsmentioning
confidence: 99%
“…Six of these regions are based on a series of prior studies with healthy adults and those with non-Alzheimer dementia (Garrido et al ., 2008; Phillips et al ., 2015; Rosch et al ., 2019; Adams et al ., 2021). We extended the network to include the inferior parietal cortex (Lappe et al ., 2013), given the impact of Alzheimer’s disease on parietal cortex (Jacobs et al ., 2012; Talwar et al ., 2021) and recent evidence of mismatch negativity responses from parietal cortex (Lappe et al ., 2013; Cope et al ., 2022). We defined multiple, alternative, symmetric model architectures, each representing plausible alternative hierarchical relationships between regions and their connectivity to include the inferior parietal cortex ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Twenty individuals per group are in line with previous neurophysiological studies of crossover drug-placebo effects of bvFTD and PSP [ 8 , 75 ], and memantine in schizophrenia [ 41 ]. Using a different mismatch paradigm, Cope et al [ 76 ] and Hughes et al [ 9 ] reported 30–40% reductions in amplitude with bvFTD (Cohen’s d > 1.6). In this context, for frequentists tests, N = 20 provides >80% power with alpha 0.05 to detect a restorative crossover drug intervention versus placebo with effect size d ≥ 0.6 [ 77 ] (noting the smaller d = 0.3 reported by [ 41 ] in control participants); and >80% power with alpha 0.05 to detect a correlation r ≥ 0.5 with GABA.…”
Section: Methodsmentioning
confidence: 99%